1993
DOI: 10.1002/jbm.820270108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mineral content and composition on graylevels in backscattered electron images of bone

Abstract: To determine the meaning of graylevels in backscattered electron (BSE) images of actual bone tissues, the influence of mineral content and mineral composition on BSE image graylevels was studied using chick bone tissue representing a broad age range. These tissues were analyzed for BSE image graylevels, Ca/P molar ratios, mineral composition mineral content (v/v), ash fraction (w/w), and density (g/cm3). Linear regression analyses showed that the weighted mean graylevels (WMGLs) in BSE images were positively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 22 publications
5
74
0
Order By: Relevance
“…Well known is that the different mineral phases in a cement matrix exhibit different grey levels in the BSE images. Skedros et al (1993) and Ye (2003) demonstrated that the grey-scale level in BSE images corresponds to the average atomic number and mineral density of each phase. Based on these well-known dependencies and considering the BSE images obtained in the present study, the main mineral phases in both OPC and OPCv can be distinguished by the order of grey-scale intensity values as follows: UC > CH > HD CSH > LD CSH > pore structures.…”
Section: Capillary Pore Structurementioning
confidence: 99%
“…Well known is that the different mineral phases in a cement matrix exhibit different grey levels in the BSE images. Skedros et al (1993) and Ye (2003) demonstrated that the grey-scale level in BSE images corresponds to the average atomic number and mineral density of each phase. Based on these well-known dependencies and considering the BSE images obtained in the present study, the main mineral phases in both OPC and OPCv can be distinguished by the order of grey-scale intensity values as follows: UC > CH > HD CSH > LD CSH > pore structures.…”
Section: Capillary Pore Structurementioning
confidence: 99%
“…Residual chloroform was removed by placing the specimens in an 80°C oven for 5 days. Following defatting and drying, each bone segment was weighed using a precision analytical balance (Mettler H51; Mettler Instruments Corp., Hightstown, NJ) and then placed in a furnace at 550°C for 24 hr to remove organic constituents (Gong et al, 1964;Skedros et al, 1993b). The bone specimens were weighed again after ashing.…”
Section: Mineral Standards/ash Measurementsmentioning
confidence: 99%
“…A comparison of mineralisation densities in bone at high spatial resolution can be performed by quantitative backscattered electron (BSE) image analysis in the scanning electron microscope (Boyde et al 1983 ;Skedros et al 1993 ;Boyde & Jones, 1996 ;Bloebaum et al 1997 ;Roschger et al 1997Roschger et al , 1998Kingsmill & Boyde, 1998). In addition to the mineralisation data, histological information is also provided by this method.…”
Section: mentioning
confidence: 99%